Yield and quality of common bean cultivated on grass straws and fertilized with nitrogen under no-tillage - Amaral, Camila Baptista do [UNESP]; Pinto, Carolina Cipriano [UNESP]; Flores, Jordana de Araujo [UNESP]; Cecchio Mingotteo, Fabio Luiz [UNESP]; Lemos, Leandro Borges [UNESP]; Fornasieri Filho, Domingos [UNESP] (Empresa Brasil Pesq Agropec, 2016)
The objective of this work was to evaluate the effect of top-dressed nitrogen fertilization and of the straws of corn crop, of corn intercropped with Brachiaria, and of Brachiaria on grain yield and quality of common bean. The experiment was carried out under irrigation, in winter cropping, after five years from the implementation of a no-tillage system, in a clayey Oxisol. A randomized block design with split plots and three replicates was used. The plots consisted of the straws of corn, of corn intercropped with Brachiaria, and of Brachiaria; while the split plots consisted of top-dressed N at levels corresponding to 0, 40, 80, 120, and 160 kg ha(-1). All the treatments received 17 kg ha(-1) N at sowing. Common bean cropped over Brachiaria straw reaches higher grain yield and has increased agronomic efficiency. The evaluated straws did not affect the qualitative attributes of common beans. The application of top-dressed N increased protein contents and cooking time of the beans, besides grain yield up to the level of 136 kg ha(-1) N.
Keywords: Phaseolus vulgaris; Urochloa ruziziensis; Zea mays; cover crops; agronomic efficiency; irrigated common beans; cooking time